The Effect of Leaflet on Reproductive Health Media Accessing Behavior among Students in Medan North Sumatera - Veronica Anggreni Damanik; Sri Lasmawanti; Novita Anggraini; Bangun Dwi Hardika (Journal of Health Promotion and Behavior, 2020)
Background: Psychological changes in adolescents can be influenced due to hormonal changes in the body and the desire to express sexual appetite so that it can result in increased sexual problems such as increased premarital sexual behavior or free sex. Therefore, it is necessary to do an intervention step to be able to increase information and knowledge for adolescents about reproductive health. This study aimed to determine the effect of information through leaflets on the habit of accessing media related to reproductive health and premarital sexual attitudes on students at Vocational School (VS) Parulian I Medan.Subjects and Method: This was quasi experimental with One Group Pretest-Postest Design without a control group. The study was conducted from May to July 2019. A total of 133 studentsof class X and XI of Medan Parulian I Vocational School was selected for this study. The data were collected using a questionnaire. The data was analyzed by Wilcoxon.Results: The habit of accessing media after being given information through leaflets (Mean= 1.59; SD= 0.49) was higher compared to before getting information through leaflets (Mean= 1.26; SD= 0.44), and statistically significant (p<0.001). Pre-sexual behavior marriage after got the information through leaflets (Mean= 42.38; SD= 11.11) was higher than before got the information through leaflets (Mean= 38.92; SD=11.97), and statistically significant (p<0.001).Conclusion: Information in the leaflet improved the habit of accessing media related to reproductive health and positive premarital sexual attitudes.Keywords: leaflets, media access, premarital sexual attitudeCorrespondence: Veronica Anggreni Damanik. Nursing Study Program, Faculty of Pharmacy and Health, Helvetia Health Institute Medan. Jl. Kapten Sumarsono 107, Medan, North Sumatera. Email: veronica.damanik88@gmail.com. Mobile: 081367579723Journal of Health Promotion and Behavior (2020), 5(1): 18-25https://doi.org/10.26911/thejhpb.2020.05.01.03